The Assessment, Strategy, and Treatment Protocol: Nasolabial Fold Assessment, Strategy, and Treatment With Hyaluronic Acid Fillers in Chinese Patients - Qin Li, MD; Haiyan Cui, MD; Fang-Wen Tseng, MD; Qingyang Liu, MD; Zhiqiang Xue, MD; Jani van Loghem, MD; Kai-Chih Hung, MD; Lijun Zhou, MD; Wen Xie, MD; Jingjing Zhao, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Causes contributing to nasolabial fold (NLF) appearance can be multifactorial, hence requiring distinct dermal filler strategies. We devised 4 assessment, strategy, and treatment (AST) injection protocols, incorporating NLF etiology and severity, patient expectations, and the selection of Belotero Balance Lidocaine (BBL) and Belotero Volume Lidocaine (BVL) hyaluronic acid fillers. Methods:. The underlying etiology and photonumeric assessments of NLF severity guided protocol selection. In protocol 1, the NLF was injected directly with BBL into the mid-to-deep dermis and/or immediate subdermal plane. In protocol 2, BVL was injected using dual-plane sandwich technique into the canine fossa and subcutaneous layers. Protocol 3 combined indirect injections of BVL into the deep medial cheek fat compartment and preauricular hollows to lift ptotic soft tissue, followed by direct NLF injections with protocols 1 and 2. In protocol 4, BVL was injected into the temple and/or jawline, in combination with midface augmentation (AST protocol 3) and direct NLF injections (AST protocols 1 and 2) to fully address all underlying etiologies contributing to NLF appearance. Results:. AST protocols facilitate treatment customization to each patient’s NLF etiology and severity through direct and indirect approaches. At 30 days, NLF severity improved visibly and satisfactorily. Improvements varied from effacement of superficial nasolabial wrinkles to shallower NLF depth, improvement in cheek projection and nasojugal groove appearance, and smoother submalar contours. Conclusions:. The AST protocols provide a strategic reference for combining BBL and BVL in a personalized patient-centric approach for effective, holistic, and balanced NLF corrections and pan-facial aesthetic improvements.